Optimization of biogas from corn stover using liquid and solid-state anaerobic digestion - Lukhi Mulia Shitophyta; Muhammad Hanafi; Yusuf Eko Nugroho (Universitas Muhammadiyah Metro, 2020)
The shortage of fossil fuel can be minimized by developing renewable energies such as biogas. The raw material of biogas can be derived from corn stover. Biogas was produced under solid-state anaerobic digestion (SS-AD) and liquid anaerobic digestion (L-AD). The objectives of this study were to compare the biogas yield and analyze the pH value and VS degradation. The results reported that the SS-AD generated a higher biogas yield than L-AD. SS-AD could improve the biogas yield of 71%. Both SS-AD and L-AD had a higher final pH than the initial pH. Moreover, the VS degradation was proportionate to the biogas yield. The highest VS reduction was achieved on SS-AD. Keywords: anaerobic digestion, biogas, liquid state, solid state, volatile solid, renewable energy